Methamphetamine-Induced Sleep Impairments and Subsequent Slow-Wave and Rapid Eye Movement Sleep Rebound in Male Rhesus Monkeys - Berro, Laís F.; Overton, John S.; Rowlett, James K. (Frontiers in Neuroscience, 2022)
Use of amphetamine-type stimulants is associated with numerous adverse health outcomes, with disturbed sleep being one of the most prominent consequences of methamphetamine use. However, the extent to which methamphetamine alters sleep architecture, and whether methamphetamine-induced sleep impairment is associated with next-day sleep rebound effects, has received relatively little investigation. In the present study, we investigated the effects of acute morning methamphetamine administration on sleep parameters in adult male rhesus monkeys (N=4) using a fully-implantable telemetry system. Monkeys were prepared with telemetry devices that continuously monitored electroencephalography (EEG), electromyography (EMG) and electrooculography (EOG) throughout the night. We investigated the effects of morning (10h00) administration of methamphetamine (0.01 – 0.3 mg/kg, i.m.) on sleep during the night of the injection. In addition, we investigated sleep during the subsequent night in order to assess the possible emergence of sleep rebound effects. Methamphetamine administration dose-dependently increased sleep latency and wake time after sleep onset (WASO). Methamphetamine also decreased total sleep time, which was reflected by a decrease in total time spent in N2, slow-wave (N3) and REM sleep stages, while increasing the percentage of total sleep time spent in sleep stage N1. Importantly, methamphetamine decreased time spent in N3 and REM sleep even at doses that did not significantly decrease total sleep time. Sleep rebound effects were observed on the second night after methamphetamine administration, with increased total sleep time reflected by a selective increase in time spent in sleep stages N3 and REM, as well as a decrease in REM sleep latency. Our findings show that methamphetamine administered 8h prior to the inactive (dark) phase induces marked changes in sleep architecture in rhesus monkeys, even at doses that do not change sleep duration, and that sleep rebound effects are observed the following day for both N3 and REM sleep stages.